Acting for normative reasons and the correspondence relation. (4th May 2021) - Eslami, Seyyed Mohsen
ABSTRACT: The possibility of acting for normative reasons calls for explanation, considering that such reasons are facts. Facing this issue, some argue that to act for a normative reason, the normative reason and the reason we act for (i.e. the motivating reason) need to be identical. Others reject the idea that normative reasons are facts in the first place. A conciliatory proposal is that by appealing to dispositions we can simultaneously accept that normative reasons are facts and that we can act for them, without accepting the identity of the normative reasons and the motivating reason. After sketching an example of such a view, I mention an obstacle on its way. This view relies heavily on the correspondence relation, to make the action connected to the normative reason via a descriptive belief. It is argued that this is challenging since the correspondence relation might not be suitable to play the metaphysical role needed.